Challenges and perspectives with understanding the concept of mental fatigue - Oliver, Liam; Goodman, Stephen; Sullivan, John; Peake, Jonathan; Kelly, Vincent (International Journal of Sports Medicine, 2025)
Mental fatigue is referred to as a psychophysiological or neurobiological state caused by prolonged periods of demanding cognitive activity. Sport and exercise science research studies have investigated the effects of experimentally induced mental fatigue on cognitive performance, with mixed results. It has been suggested that negative effects of mental fatigue on cognition performance in laboratory studies could translate to impaired sport performance. However, it remains unclear if impairments in sport performance are due to mental fatigue and how mental fatigue may differ from physical fatigue. Fatigue is well understood as a complex multifactorial construct involving interactions between physiological and neuropsychological responses across brain regions. It may be prudent for researchers to return to the origins of fatigue and cognition before attempting to connect mental fatigue and sport cognition. This article reviews the concept of mental fatigue, its mechanisms and neuroanatomical basis, models of cognition relevant to sports science, investigates how mental fatigue may influence cognition, and suggests future research directions. Mental fatigue as a construct separated from fatigue could be an oversight that has hindered the development of our understanding of mental fatigue. Future sports science research could work to enhance our knowledge of our definitions of fatigue.
Keywords: cognition; cognitive fatigue; cognitive performance; fatigue; mental fatigue; neuropsychology